(untitled) (Research, Society and Development, 2024)
Objective: To describe the clinical and epidemiological profile of patients diagnosed with acute aortic syndromes in a cardiovascular reference service in the city of Belém – Pará. Methodology: This is a descriptive study of 12 patients admitted to the Hospital de Clínicas Gaspar Vianna, in the period from March to December 2023. Variables related to age, sex, education, origin, symptoms on admission, characteristic of pain on admission, presence of pulses in the upper and lower limbs, type of aortic syndrome, Stanford and DeBakey classification, were considered. whether surgery was necessary, comorbidities, complications, length of stay and outcomes. Results: Chest pain was present in all patients in the sample and most of them were sudden. There was a pulse in the upper and lower limbs. The most common type of aortic syndrome was acute dissection. Stanford’s A rating was the most frequent. In the DeBakey classification there was a greater proportion of classes I and III. Among the participants, 07 required surgery, and the most frequent was Bentall. Among the comorbidities mentioned, SAH had the highest proportion. Sepsis was the most frequent complication, followed by AKI, Hematesis and DHE. Conclusion: Half of the patients had death as an outcome. More studies are needed about this pathology, as well as greater prevention of the disease’s risk factors to promote continued education for emergency and first aid teams in order to reduce deaths and complications in patients diagnosed with this syndrome.